Pension Reforms in the Nordic Countries and Germany: Conference Proceedings of the 2024 Annual Meeting of the German Society for Demography (DGD) by the Working Group on Demographic and Social Developments - Christina Benita Wilke; KompetenzCentrum für angewandte Volkswirtschaftslehre (KCV) FOM Hochschule für Oekonomie & Management (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2024)
This volume documents excerpts from our session on pension reforms in the Nordic countries and Germany at the Annual Meeting of the DGD at the University of Hamburg in March 2024. Pension systems in Germany as well as the Nordic countries have been subject to substantial pension reforms in the past decades, foremost in order to respond to the demographic challenges these nations face. Both regions are experiencing aging populations, which puts pressure on public pension systems and requires innovative reform strategies to ensure sustainability. Although Germany and the Nordic countries share a history of strong welfare states, their approaches to pensions vary - offering valuable lessons in policy design, from the Nordic countries' rather flexible pension ages to Germany's evolving multipillar system. Looking forward, there is a need for further reforms that adapt to evolving demographic trends, ensure intergenerational fairness, and maintain fiscal sustainability, while also addressing new challenges such as digitalization and changing work patterns. (...)
Keywords: 330; Pension; Pension reforms; Nordic Countries; demographic and social developments; retirement